(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Paper presents results of air ionization level measurements made in past 3 years in Rezekne city. The concentrations of positive and negative air ions with mobility factor k ≥ 0,4 cm2/V·s were obtained by portative air-ion counter “Sapfir-3M” (Russia) in 8 parts of the city thrice per day. The approximate interconnections among ionization and chemical and mechanical pollution of air were analyzed. The complex evaluation of long – term air pollution impact on different parts of city is carried out using methods of lichenoindication and air ion research.